Greatnesses and misfortunes of the Amazon Rainforest: The construction of purposes and the representation of interests in the latest political debates - Grill, Igor Gastal; Reis, Eliana Tavares dos (FCL-UNESP Laboratório Editorial, 2021)
At the Brazilian recent public scenario, besides the complexity of matters and the spread of spokespeople engaged in defending the Amazon rainforest both in transnational and national spheres, the outlining of a series of controversies about reasons, responsibility and ways to fight against ongoing wildfires and deforestation in the ‘’region’’ was merged. Taking for examination the items of news published on digital media (among other materials) it is possible to perceive emplacement and position taking from collective and individual agents, having placed themselves on opposite and unset (ambivalent at times) sides of the conflicts/debates triggered since 2018 presidential election. We mainly considered the actions of leaders from parliamentary fronts and interest groups, observing discourses, assets and register categories, competing or relationally called on in order to intervene and define the foundations of a cause or legitimate problematic. Thus, it is aimed to unveil intervener principles in the alignments which have marked the feud in a context thought to be ‘’critical’’.